(3JMdjd hJbjje OhQ GdHfhc aj ecGaMI YedjGJ ZSjd GdGehGds - (3eMehO eMeO(B, (3SYjaGfs ((3YeGf(B:s (3OGQ GdKbGaI(B,s, 2008)
(3fXQkG ddBKGQ GdVGQI dXGgQI ZSjd GdCehGd Ydi GdGbJUGO GdhWfj hGdYGdej, heG JMOKg gPg GdXGgQI ef RYRYI ddKbI aj GdeDSSGJ GdeGdjI abO CUHMJ ehGLgJgG ef ChdhjGJ GdSdWGJ GdJTQjYjI, hGdQbGHjI Ydi fWGb GdYGde, ceG Cf GdJWhQGJ GdeJSGQYI GdJj TgOJgG GdHfhc hGdeDSSGJ GdeGdjI aj fhGMj GdQHW GdEdcJQhfj hGdhSGFd GdeUQajI GdCNQi jLYd Jdc GdeDSSGJ CcKQ YQVI ddGSJZdGd aj YedjGJ ZSjd GdCehGd(B. (3heY JCcjO CgejI GdJfHjg dNWhQI GdOhQ GdPj jfgV Hg GdHfc aj eQGMd ZSjd GdCehGd GdKdGK(B: (3GdEjOGY, hGdJZWjI, h GdOeL aEfg dG HO ef JMdjd GdVhGHW GdMGdjI heMGhdI hVY VhGHW JMce gPg GdXGgQI(B. (3ceG Cfg dG HO ef HjGf GdOhQ GdNWjQ GdPj jfgV Hg GdHfc aj ecGaMI gPg GdXGgQI, heMGhdI JMdjd GdELQGAGJ GdOGNdjI ddHfhc, hHjGf eG EPG cGfJ gPg GdELQGAGJ cGajI decGaMI gPg GdXGgQI Ce dG ? EVGaI Edi hVY JUhQGJ YedjI aj eLGd GdYed GdeUQaj dehGLgI gPg GdXGgQI GdNWjQI, h eG jfYcS EjLGHG Ydi Jbhje GdhSGFd GdeJHYI ef pbHd GdHfhc GdCQOfjI ShGA HGdhSGFd GdhbGFjI Ch GdYdGLjI dehGLgI XGgQI ZSjd GdCehGd hhVY GdJhUjGJ GdefGSHI dJLfH gPg GdXGgQI(B.s
(3HjHdjhZQGajG U(B. 279s
Keywords: (3Hfhcs; (3LQGFe GdGbJUGOs; (3ZSjd GdGehGds